Microbial dynamics and physico-chemical properties of soil in the rhizosphere of chrysanthemum (Dendranthema grandiflora) as influenced by integrated nutrient management - LAISHRAM, NOMITA; DHIMAN, S R; GUPTA, Y C; BHARDWAJ, S K; SINGH, ARVINDER (The Indian Journal of Agricultural Sciences, 2026)
Soil physico-chemical properties and microbial population were assessed to get the knowledge of the effect of integrated nutrient management in chrysanthemum (Dendranthema grandiflora Tzvelev) flower production system in the mid-hill conditions of Himachal Pradesh. Plants of chrysanthemum cultivars Purnima and Ajay were grown in open field condition with 17 different nutritional regimes during 2009 and 2010. The experiment was laid out in factorial randomized block design, replicated thrice. Findings revealed highest amount of available soil N (373.04 kg/ha), K (283.18 kg/ha) and organic carbon content (1.260 %) in the plots receiving 30 g/m2 each of NPK + vermicompost (1 kg/m2) + biofertilizers. Maximum available soil P (39.86 kg/ha) was recorded with the application of 22.5 g/m2 each of NPK + vermicompost (1kg/m2) + biofertilizers. No significant change was observed in soil pH and electrical conductivity due to different treatments. Azotobacter population (10.50 Ã— 106 cfu/g of soil) and phosphorus solubilizing bacterial count (12.83 Ã— 106 cfu/g of soil) were maximum with the application of 15 g/m2 each of NPK + vermicompost (1 kg/m2) + biofertilizers. However, maximum arbuscular mycorrhizal fungi spore count (196.58 per 20 g of soil) was observed with the application of vermicompost (1 kg/m2) + biofertilizers. The overall multifaceted effects of different integrated nutrient management treatments that facilitated beneficial soil conditions in the present study also reflected the significant increase in the flower yields of both Purnima and Ajay even over the ad-hoc recommended treatment (30 g/m2 each of NPK).